PENINGKATAN KETERAMPILAN MENULIS KONJUNGSI DENGAN MODEL PjBL BERBASIS PENDEKATAN TaRL MELALUI STORYBOARD DI KELAS IV SDN SUMURWELUT III/440 SURABAYA - Syahla Muthia Eronisa; Putri Dyah Ayu Nur Evitasari; Risty Amaria Ayuningtyas; Rizki Chusnul Hidayah; Muhammad Alfan Khoirush Shidqi; Riski Kurniawan; Rarasaning Satianingsih; Ratnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low conjunction writing skills of fourth-grade students at SDN Sumurwelut III/440 Surabaya in the Indonesian Language subject. Based on initial observations, most students had not been able to use conjunctions correctly in sentences and paragraphs. This study aims to improve conjunction writing skills through the application of the Project Based Learning (PjBL) model based on the Teaching at the Right Level (TaRL) approach using storyboard media. This study is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The subjects were 29 fourth-grade students divided into three ability levels based on the TaRL approach, with a Minimum Completion Criteria (KKM) of 75. The results show an improvement in conjunction writing skills. In Cycle I, the class average score reached 67.68 with a classical completion percentage of 42.9% (12 out of 28 students). In Cycle II, the class average score increased to 75.57 with a classical completion percentage of 67.9% (19 out of 28 students). This improvement occurred along with better implementation of the PjBL model with storyboard media that was more structured and contextual according to students' ability levels.